Asian international students' help-seeking intentions and behavior in American Postsecondary Institutions. (January 2021) - Xiong, Yiying; Yang, Lijing
Abstract: While the number of Asian international students has increased in postsecondary institutions in the United States over the last two decades, unlike their American peers, these students were reported to have more severe mental health issues with less help-seeking intentions and behavior. This study drew the national data collected by American College Health Association-National College Health Assessment (ACHA-NCHA) from 2011 to 2014 to examine how various factors were associated with help-seeking intentions and behavior among Asian International Students (AIS) in the U.S. After case-wise deletion of missing data, the dataset used in regression analyses included 97, 259 college students, including 2999 AISs, who were randomly drawn within the 62 participated postsecondary institutions. The study performed a series of logistic regression with complex survey design that controlled for institutional clustering effects to analyze the relationship between various factors and AISs' help-seeking intentions and behavior. The results showed that AIS utilized significantly less services and were less willing to seek mental health services than not only American domestic students but also other international students. Variables related to institutional characteristics, demographic information, academic status, and health conditions were found to significantly influence AISs' help-seeking intentions and behavior. College mental health professionals and university stakeholders need to pay more attention to the mental health needs of AIS. Implications for college mental health professionals and university stakeholders are discussed.